2017
DOI: 10.7205/milmed-d-16-00191
|View full text |Cite
|
Sign up to set email alerts
|

Examining Associations Between Relocation, Continuity of Care, and Patient Satisfaction in Military Spouses

Abstract: No studies have previously been conducted to determine why military health system beneficiaries are less satisfied with care than their civilian counterparts. Discontinuous care is an ongoing issue for military families, which can impact satisfaction and potentially lead to poorer health outcomes. Although the military culture may not allow for fewer relocations, these results indicate that taking steps to promote enduring, trusting relationships with primary care providers may improve patient satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Provider satisfaction rates regarding seeing incorrectly scheduled patients in the clinic and scheduling errors in the clinic both increased by 0.75 after implementation of standardized documentation. These findings are consistent with published literature, which supports that discontinuity of care and negativity in the workplace impact providers (Gleason & Beck, 2017; Volpe et al, 2014; Yanchus et al, 2017). Although the scores for APPs regarding intent to leave the organization because of scheduling issues remained high before and after the intervention, the concern remains that prolonged dissatisfaction of providers can result in employee turnover, increased cost to the organization, and diminished patient care (Schwartz et al, 2021; Wang et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Provider satisfaction rates regarding seeing incorrectly scheduled patients in the clinic and scheduling errors in the clinic both increased by 0.75 after implementation of standardized documentation. These findings are consistent with published literature, which supports that discontinuity of care and negativity in the workplace impact providers (Gleason & Beck, 2017; Volpe et al, 2014; Yanchus et al, 2017). Although the scores for APPs regarding intent to leave the organization because of scheduling issues remained high before and after the intervention, the concern remains that prolonged dissatisfaction of providers can result in employee turnover, increased cost to the organization, and diminished patient care (Schwartz et al, 2021; Wang et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…To support access to timely care, providers continue to see incorrectly scheduled patients. Incorrectly scheduled patients disrupt continuity of care and contribute to provider frustration, which may negatively affect patient satisfaction and perceived quality of care (Fan et al, 2005; Gleason & Beck, 2017; Wetmore et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The MK-8591-eluting PrEP implants have also achieved promising preliminary results [ 55 ], with clear benefit over daily tablet for individuals with adherence concerns or an unpredictable work schedule [ 56 ]. The expeditionary nature often entails military members to relocate, deploy, or miss regular follow-up appointments [ 57 , 58 ]. Therefore, availability of longer-acting PrEP modalities should be an important component of the future PrEP programs for military members.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies have shown that physicians tend to overestimate their practice acceptance rates for new patients based on insurance type [ 14 , 15 ]. The difficulty in finding available providers and the lack of providers accepting this particular insurance creates a barrier in maintaining continuous care for this population [ 12 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%